Fiscal Decentralization and Regional Economic Growth: Evidence from the Riau Islands Province, Indonesia (2017–2024) - Dessy Rachmawatie; Rifki Amriza (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study analyzes the effect of fiscal decentralization on economic growth in the Riau Islands Province for the period 2017–2024. Using panel data from seven districts/cities and a Fixed Effects Model (FEM), the variables tested include Regional Original Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on Regional Gross Regional Domestic Product (GRDP). The results show that fiscal instruments simultaneously have a significant effect on GRDP, with a model clarity of 99.88%. Partially, Regional Original Revenue (PAD) and General Allocation Fund (DAU) have a positive and significant effect, with DAU being the most dominant driving factor. Conversely, Regional Revenue (DBH) has no significant effect, while Special Allocation Fund (DAK) has a negative effect due to its allocation focus on long-term physical development. These findings emphasize the importance of fiscal independence and optimization of central transfer funds to stimulate economic growth in the archipelago.